Performing Dissent: Pete Seeger and Paul Robeson before HUAC (1955-1956) - Jodie Childers (Transatlantica)
In this paper, I argue that the testimonies delivered by Pete Seeger and Paul Robeson before the House Un-American Activities Committee (HUAC) shed light on how left-wing artists performed their radical identities in response to allegations of un-Americanism during the height of McCarthyism. Situating Seeger’s and Robeson’s testimonies within their respective biographical contexts, I offer a close reading of these two documents in juxtaposition, analyzing them not only as historical archives but as rhetorical performances that illustrate how Seeger and Robeson conceptualized national identity while also addressing internationalist concerns. The methods that Seeger and Robeson employed to attack the committee are historically significant. While Seeger’s testimony in August 1955 championed individual liberty and freedom of speech, using the First Amendment as the foundation for his position, Robeson’s testimony delivered in June 1956 invoked an internationalist sense of social justice, linking left-wing politics, the civil rights movement within the United States, and decolonization efforts around the world.